1999
DOI: 10.1161/01.cir.100.11.1209
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Stroke Incidence in Male Smokers

Abstract: Alcohol consumption may have a distinct dose-response relationship within each stroke subtype-linear in subarachnoid hemorrhage, U-shaped in intracerebral hemorrhage, and J-shaped in cerebral infarction-but further studies are warranted. Systolic blood pressure and HDL cholesterol seem to mediate the effect of alcohol on stroke incidence, but evidently additional mechanisms are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 39 publications
1
34
1
Order By: Relevance
“…The monotonic increasing trend of mortality with high GGT levels is unlikely to simply reflect the effects of alcohol consumption 16 because most studies have shown a U-or J-shaped relationship of alcohol drinking to cardiovascular 17,18 and all-cause mortality. 19 There is evidence supporting a mild to moderate independent beneficial effect of alcohol consumption on CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…The monotonic increasing trend of mortality with high GGT levels is unlikely to simply reflect the effects of alcohol consumption 16 because most studies have shown a U-or J-shaped relationship of alcohol drinking to cardiovascular 17,18 and all-cause mortality. 19 There is evidence supporting a mild to moderate independent beneficial effect of alcohol consumption on CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…In total, during 1980 -1998, 37% of patients with aneurysmal SAH died within 3 months. Hypertension, 6,47-51 cigarette smoking, 6,47,48,50,52-60 and alcohol consumption 6,50,55,57,61 have been studied as independent risk factors for SAH. The risk of SAH was especially high among lean hypertensive subjects and lean smoking subjects, that is, BMI was inversely associated with the risk of SAH.…”
Section: Inagawa Incidence and Case Fatality Rates Of Aneurysmal Sahmentioning
confidence: 99%
“…Alcohol has been consistently associated with a reduced risk of CAD (Agarwal, 2002). Most prospective and retrospective studies have reported an alcohol-induced reduction in cardiovascular risk (Boffetta & Garfinkel, 1990;Wannamethee & Sharper, 1998;Leppala et al 1999;White et al 2002). During the last 20 years the level of alcohol that has been shown to be associated with a reduced cardiovascular risk has declined from moderate amounts (20-30 g/d) to small amounts (5-15 g/d).…”
Section: Alcohol and Coronary Artery Diseasementioning
confidence: 99%
“…Despite the well-known negative as well as positive aspects of its role in the pathogenesis of different chronic diseases such as coronary artery disease (CAD) or cancer (Leppala et al 1999;MacDonald, 1999;Ruf, 1999;Suter, 2001a;Mukamal et al 2003), the controversy about the 'ideal' intake of alcohol for health maintenance continues.…”
mentioning
confidence: 99%